An efficient and automated P2P overlay system for network monitoring - Mendonca, Ricardo (2020)
Precise and efficient monitoring is vital to ensure that a network works according to the intended behaviour, as well as quickly acting in response to possible problems. The task of monitoring a network becomes complex with increasing network size and its heterogeneity. This work explores the development of a Peer-to-Peer (P2P) system to monitor network communication infrastructures. All the processes of creation of the system and the existing entities will be described as well as their communication capabilities. Then, the definition of a metalanguage will be exposed, allowing network administrators to conFigure and pre-program the network in an effective and versatile manner. The optimization of the monitoring system will be also described, reducing the traffic generated by the P2P network. It will be also addressed how the system became fault-tolerant, recovering its state even if any entity has a problem.